History of Katerinoslav histological school (to 100 years anniversary of histology department of Dnipropetrovsk medical academy). Part ІII: from 2000 to the present - D. G. Marchenko; S. B. Morozova; N. S. Petruk; O. Yu. Pototska; L. A. Romanenko; N. V. Stanishevska; N. M. Sultanova; I. S. Khripkov; K. M. Shevchenko; I. V. Tverdokhlib; L. A. Filimonova (Морфологія, 2018)
The current stage of the development of the Department of Histology began in 1999, when the decision of the administration of the institution and the Ministry of Health of Ukraine restored its independent status.